Níveis de Beta-Defensinas no fluido crevicular gengival de indivíduos com periodontite crônica e Diabetes Mellitus Tipo 2 - Alexandre Godinho Pereira (2018)
Crevicular fluid levels of beta-defensins in individuals with chronic periodontitis and type 2 diabetes Scientific evidence indicates a bidirectional relationship between chronic periodontitis and Type 2 Diabetes Mellitus (DM2). Recent studies have shown that components of the innate immune response, such as human beta-defensins (hBDs), may be altered in individuals with CP or DM2. Given that the innate immune response is the body's first defense barrier against microbial invasion, changes in hBDs could partially account for an increase in the susceptibility CP. The present study had 2 research proposals with specific objectives: (1) to evaluate the influence of periodontitis and inflammatory site condition on hDBs-2 and -3 levels in the gingival crevicular fluid (GCF) of individuals with and without periodontitis; and (2) to assess the influence of DM2 and glycemic control on the levels of hBDs-1, -2 and -3 in the GCF of individuals with and without DM2. For the proposal 1, healthy subjects (H) and subjects with periodontitis (P) were selected among the patients from the School of Dentistry of the Federal University of Minas Gerais. For the proposal 2, individuals with DM2 with good (DM2g) and poor (DM2p) glycemic control were selected among the users of the public health system of the metropolitan area of Belo Horizonte, comprising 20 individuals in each group. All subjects underwent complete periodontal examination and medical and sociodemographic data were recorded. GCF samples were collected in healthy sites (Hh) from subjects without periodontitis; samples of healthy sites (Ph), gingivitis (Pg) and periodontitis (Pp) were collected from individuals with periodontitis. Quantification of hBDs in the GCF was performed by the Enzyme Linked ImmunonoSorbent Assay (ELISA) sandwich method. The present study was approved by the Research Ethics Committee of the Federal University of Minas Gerais - COEP UFMG (CAAE # 0529.0.203.0001-11). Levels of hBDs were compared among healthy sites, sites with gingivitis and sites with periodontitis, nested in individuals with and without periodontitis, through linear hierarchical modeling. Levels of hBDs were compared between healthy subjects, with DM2 with good and poor glycemic control through the Kruskal-Wallis test followed by Dunn's post-hoc test for pair-wise comparisons. Results showed that periodontitis was associated with high levels of hBD-2 (coefficient 14.68, p = 0.023) and hBD-3 (coefficient 1091.86, p <0.001) at the individual level. However, there was no effect of the site condition on these levels. It was also demonstrated that DM2, regardless of the glycemic control, was associated with reduced levels of hBD-1 (p <0.001), that DM2p was associated with reduced levels of hBD-2 (p <0.01); and that DM2 did not result in changes in hBD-3 values. Increased expression of hBD-2 and -3 in the GCF of individuals with periodontitis may suggest either a normal response of the organism to the infection of the gingival tissues or can be considered a partially responsible factor for the exacerbated immunoinflammatory response commonly found in individuals with periodontitis. DM2 appears to affect the expression pattern of hBD-1 and -2 differently.